"Human kind Cannot bear very much reality": the relationship between John Ruskin's visionary aspiration and his mental health. Issue 3 (16th March 2022) - Collicutt, Joanna
ABSTRACT: John Ruskin was a Victorian polymath who developed severe mental health problems from late middle age. This paper focuses on one of his many areas of interest and expertise, visual aesthetics. It traces the relationship between his theories and practices in this area and the nature of his mental health condition, which was dominated by visual symptoms. It argues that Ruskin's aesthetic theory is part of a broader spiritual visionary quest, firmly framed within the Christian theological tradition, and that it valorises certain habits of perception and attention that are now recognised to be a feature of cognition in psychosis. It suggests that there is continuity, if not a causal relationship, between Ruskin's lifelong adoption of these practices and the psychological symptoms he displayed as his (probably neuropsychiatric) illness progressed.